Styridsat rokov ceskoslovenskej transfúznej sluzby - Hrubisko, M; Kvasnicka, J (Casopis lekaru ceskych, 1989)
The authors analyze the development and creation of the concept of a uniformly organized blood transfusion service in the CSSR from its beginning to the present time. For the needs of the Czechoslovak socialist health services it proved expedient to integrate haemotherapeutic care in a common department of haematology and transfusiology, in a network of common sections of haematology and blood transfusion and to focus the transfusion service on clinical work. On average there is one common department for a population of 135,000 which ensures blood transfusions as well as haematological work and there is one doctor specialized in haematology and transfusiology per 48,000 population. Blood donorship in the CSSR for basic needs of the transfusion service is not paid; it is organized by the Czechoslovak Red Cross. On average 35,000 units of blood per 1 million inhabitants are collected per year. Component haemotherapy predominates; only 20-25% of the production is used for transfusions of whole blood. The ratio of whole blood transfusions to erythrocytes is 35:65%. The annual number of blood transfusions per hospital bed is 5 on average. The incidence of undesirable posttransfusion reactions, mainly febrile and allergic, is low, it varies between 0.2 and 0.4%. Serious haemolytic reactions are rare and occur in recent years in one patient per 100,000 transfusions. The achievement of the standard of the Czechoslovak blood transfusion service is due to the care of the two national ministries of health, the good training of workers and the clinical orientation of the performed work.
Keywords: Československo; dějiny 20. století; krevní transfuze; Humans; History, 20th Century; Blood Transfusion; lidé; Czechoslovakia